A bipolar system of copyright in the internet environment. (2016) - Papadopoulos, Marinos
In this paper, I am elaborating upon Alexander Peukert's proposal for a bipolar copyright system in the internet environment; said system focuses on securing for the right-holder the freedom to choose among given options, i.e., the author's freedom to choose between exclusive, proprietary exploitation on the basis of DRM or participating in the levy/tax system as regards non-commercial file-sharing. Peukert's proposal considers a spectrum of proposals for future copyright models regarding p2p networks that would replace exclusive rights in the copyrightable subject matter with mandatory remuneration rights. The fundamental notion of these concepts is that efficient control of the use of p2p network technology is not possible without outright banning the technology altogether or without severe drawbacks with regard to monitoring and privacy. To avoid these disadvantages, non-commercial file sharing would be legalised under a limitation of or exception from copyright. Right holders would be compensated by a levy or tax on products and services used for file-sharing. The congeniality of this solution rests upon the fact that it preserves the benefits of p2p network technologies while at the same time guaranteeing author's compensation.